Efficiency and Accessibility of Sharia Home Financing for Millennials: A Study of BSI's Griya Si Muda Program vs BTN iB Property - Fatkhurrozi, Tanto; Mugiyati (Institut Agama Islam Negeri Parepare, 2024)
Purpose – The study aims to explore how sharia-compliant home financing programs bridge affordability, Islamic values, and cultural traditions to meet millennial housing needs in Indonesia Method – Employing a qualitative approach with a literature study method, the research compares financing schemes, requirements, and benefits offered by Bank Syariah Indonesia (BSI) and Bank Tabungan Negara (BTN) Syariah. Findings –. Findings reveal that both programs integrate Islamic principles with modern financial practices, offering innovative solutions for millennials to achieve homeownership. BSI’s